Mental Health Literacy and Psychological Distress Among University Students - Muhamat Akil Shirod; Sayang Ajeng Mardhiyah (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Students at Sriwijaya University face various challenges, such as academic pressure, which can lead to psychological distress if not managed properly. Objective: This study examines the relationship between mental health literacy (MHL) and psychological distress among undergraduates at Sriwijaya University, hypothesizing that higher MHL correlates with lower distress levels. Method: Using a quantitative survey method, data were collected from 361 students and analyzed using the Pearson product-moment correlation (r = 0.122, p < 0.05), independent t-test compares two groups, while one-way ANOVA analyzes more than two groups. Results: We observed an unexpected pattern, a significant yet negligible positive correlation. This suggests students with higher MHL reported slightly greater distress, contradicting our initial hypothesis. Conclusion: Despite this unexpected association, we emphasize the continued importance of MHL education through campus programs. We recommend improvements in mental health literacy, particularly in first-aid skills, help-seeking behavior, and self-help strategies, as early protective measures in universities. Future studies should also examine additional variables that may reduce psychological distress. Abstrak Latar Belakang: Mahasiswa di Universitas Sriwijaya menghadapi berbagai tantangan seperti tekanan akademik yang dapat menyebabkan distres psikologis jika tidak dikelola dengan baik. Tujuan: Penelitian ini mengkaji hubungan antara literasi kesehatan mental (LKM) dan distres psikologis di kalangan mahasiswa Universitas Sriwijaya, dengan hipotesis bahwa LKM yang lebih tinggi berhubungan dengan tingkat distres yang lebih rendah. Metode: Menggunakan metode survei kuantitatif, data dikumpulkan dari 361 mahasiswa dan dianalisis menggunakan korelasi Pearson’s product moment (r = 0.122, p < 0.05), independent sample t-test membandingkan dua kelompok populasi, sedangkan one-way ANOVA untuk analisis lebih dari dua populasi. Hasil: Kami mengamati pola yang tidak terduga, korelasi positif yang signifikan namun dapat diabaikan antara LKM dan distres psikologis. Hal ini menunjukkan bahwa mahasiswa dengan LKM yang lebih tinggi melaporkan distres yang sedikit lebih besar, yang bertentangan dengan hipotesis kami. Kesimpulan: Meskipun ada asosiasi yang tidak terduga ini, kami menekankan pentingnya pendidikan LKM yang berkelanjutan melalui program-program kampus. Kami merekomendasikan peningkatan literasi kesehatan mental, khususnya pada aspek first aid skills and help-seeking behavior, dan self-help strategies, sebagai langkah protektif dini di lingkungan universitas. Studi selanjutnya juga perlu meneliti variabel tambahan yang dapat mengurangi tekanan psikologis.